Incidence of Nasogastric and Gastrostomy Tube at Discharge Is Reduced after Implementing an Oral Feeding Protocol in Premature (< 30 weeks) Infants - Kamitsuka, Michael D.; Nervik, Patricia A.; Nielsen, Shana L.; Clark, Reese H. (American Journal of Perinatology, 2017)
Objective Reduce the number of infants requiring home tube feeds by initiating an oral feeding protocol (OFP).Study Design All infants < 30 weeks' gestation were eligible. The OFP involved four steps: encourage non-nutritive suck before 30 weeks, oral motor exercises starting as early as 30 weeks, swallowing exercises as early as 31 weeks, and an infant-driven oral feeding pathway as early as 32 weeks.Results The study included 129 infants before the protocol (January 2010 to December 2011) and 141 infants after the protocol (March 2013 to May 2015). Between the study periods, a multidisciplinary committee took 8 months to create the OFP, followed by a 3-month orientation of the protocol to the nursing and medical staff. The incidence of home tube feeds for 23 to 29 weeks was 26% before and 15% after the protocol (p = 0.03). Oral feeds were started sooner (p < 0.001), and full oral feedings were achieved earlier after the protocol was initiated (p < 0.001).Conclusion After introducing an OFP, oral feedings were started earlier, full oral feedings were achieved sooner, and the incidence of home tube feeds at discharge was reduced.
Keywords: gastrostomy tube; nasogastric tube; feeding protocol